A q-methodology approach in determining perspectives on difficulties in mathematical problem solving among Malaysian matriculation students - Ayop, Rabiatul Adawiah (2015)
Problem solving has been emphasized in the mathematics curriculum in Malaysia at all levels including matriculation programme. However, Malaysian students were reported to have difficulties in mathematics problem solving. Therefore, students‟ perspectives on the difficulties in solving mathematics problem can give some understanding on this matter. Furthermore, there is a research gap at this level as post-secondary level is less researched compared to those of the primary and secondary education. Students‟ perspectives on the difficulties of mathematical problem solving among matriculation students were approached utilizing Q-methodology due to its appropriateness in studying perspectives. Ninety (90) matriculation students from two matriculation colleges were involved as participants. Each participants was required to rank 48 statements according to the order of agreement and disagreement for each statements about their personal views on the difficulties of mathematical problem solving. All the Q-methodology procedures: collecting concourse, developing Q-sample,selecting P-set, conducting Q-sort and analyzing data as well were done for this study. Findings showed the difficulties of mathematical problem solving occurred in four main factors namely, (1) Heuristics and Control, (2) Control and Beliefs, (3) Resources and Heuristics and (4) Resources and Beliefs. In the domain of resources, conceptual knowledge such as understanding mathematical symbols and notation showed a major load from the students. In heuristics domain, students loaded difficulties at the first stage of problem-solving phase, that is, understanding the problem and the usage of heuristics skills such as drawing diagrams or pictures in understanding the problem. In the control domain, students were found, not realizing their mistakes in a solution until they got the wrong answers. While in the beliefs domain, students were found to fear the unexpected mathematics problem. The findings may provide some benefits for future researches to focus more on matriculation students‟ ability in solving mathematical problems with more rigorous analysis.